Forming iron-rich planets with giant impacts. Issue 3 (6th July 2022) - Reinhardt, Christian; Meier, Thomas; Stadel, Joachim G; Otegi, Jon F; Helled, Ravit
ABSTRACT: We investigate mantle stripping giant impacts (GI) between super-Earths with masses between 1 and $20\, {\rm M}_{\oplus }$ . We infer new scaling laws for the mass of the largest fragment and its iron mass fraction, as well as updated fitting coefficients for the critical specific impact energy for catastrophic disruption, $Q_{{\rm RD}}^{*}$ . With these scaling laws, we derive equations that relate the impact conditions, i.e. target mass, impact velocity, and impactor-to-target mass ratio, to the mass and iron mass fraction of the largest fragment. This allows one to predict collision outcomes without performing a large suite of simulations. Using these equations we present the maximum and minimum planetary iron mass fraction as a result of collisional stripping of its mantle for a given range of impact conditions. We also infer the radius for a given mass and composition using interior structure models and compare our results to observations of metal-rich exoplanets. We find good agreement between the data and the simulated planets suggesting that GI could have played a key role in their formation. Furthermore, using our scaling laws we can further constrain the impact conditions that favour their masses and compositions. Finally, we present a flexible and easy-to-use tool that allows one to predict mass and composition of a planet after a GI for an arbitrary range of impact conditions, which, in turn, allows to assess the role of GI in observed planetary systems.